GSH-C4 Acts as Anti-inflammatory Drug in Different Models of Canonical and Cell Autonomous Inflammation Through NFκB Inhibition - Limongi, Dolores; Baldelli, Sara; Checconi, Paola; Marcocci, Maria Elena; De Chiara, Giovanna; Fraternale, Alessandra; Magnani, Mauro; Ciriolo, Maria Rosa; Palamara, Anna Teresa (Frontiers in Immunology, 2019)
An imbalance in GSH/GSSG ratio represents a triggering event in pro-inflammatory cytokine production and inflammatory response. However, the molecular mechanism(s) through which GSH regulates macrophage and cell autonomous inflammation remains not deeply understood. Here, we investigated the effects of a derivative of GSH, the N-butanoyl glutathione (GSH-C4), a cell permeable compound, on lipopolisaccharide (LPS)-stimulated murine RAW 264.7 macrophages and human macrophages. LPS alone induces a significant production of pro-inflammatory cytokines, such as IL-1β, IL-6 and TNF-α and a significant decrement of reduced GSH content. Such events were significantly abrogated by treatment with GSH-C4. Moreover, GSH-C4 was highly efficient in buffering cell autonomous inflammatory status of aged C2C12 myotubes and 3T3-L1 adipocytes by suppressing the production of pro-inflammatory cytokines. We found that inflammation was paralleled by a strong induction of the phosphorylated form of NFB, which translocates into the nucleus; a process that was also efficiently inhibited by the treatment with GSH-C4. Overall, the evidence suggests that GSH decrement is required for efficient activation of an inflammatory condition and, at the same time, GSH-C4 can be envisaged as good candidate to abrogate such process, expanding the anti-inflammatory role of this molecule in chronic inflammatory states.